Neurophotonic tools for microscopic measurements and manipulation: status report (Neurophotonics, 2022)

Roadmap on wavefront shaping and deep imaging in complex media (Journal of Physics: Photonics, 2022)
The last decade has seen the development of a wide set of tools, such as wavefront shaping, computational or fundamental methods, that allow us to understand and control light propagation in a complex medium, such as biological tissues or multimode fibers. A vibrant and diverse community is now working in this field, which has revolutionized the prospect of diffraction-limited imaging at depth in tissues. This roadmap highlights several key aspects of this fast developing field, and some of the challenges and opportunities ahead.